2010
DOI: 10.1002/jsfa.4188
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of hard wheat flour, dough and bread prepared using various processes with the addition of different phenolic acids

Abstract: Phenolic acids retain their antioxidant activity after the baking process, which has potential health benefits for consumers. Elucidation of interactions between the baking process and phenolic acids is important for the development of functional foods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
51
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 32 publications
(42 reference statements)
12
51
1
Order By: Relevance
“…These suggested that thermal treatment during baking does not give negative effect even promotes or retain the nutritional value in bread such as phenolic content and antioxidant activity. These findings are in good agreement with Han and Koh, (2011) who found that the baking process improved phenolic content and antioxidant activity in bread after baking process and this has potential health benefits for customers and food industry in terms of the development of functional foods.…”
Section: Discussionsupporting
confidence: 92%
“…These suggested that thermal treatment during baking does not give negative effect even promotes or retain the nutritional value in bread such as phenolic content and antioxidant activity. These findings are in good agreement with Han and Koh, (2011) who found that the baking process improved phenolic content and antioxidant activity in bread after baking process and this has potential health benefits for customers and food industry in terms of the development of functional foods.…”
Section: Discussionsupporting
confidence: 92%
“…Some antioxidant compounds are destroyed when baking [28]. But phenolic acids retain their antioxidant activity after the baking process [29]. However further research may be needed to evaluate the Total plate count and coliform count were high in Kohila flour while mould and yeast counts were zero, may be due to the low moisture content.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, decreases in individual insoluble bound phenolic acids during dough preparation have also been reported by Abdel-Aal and Rabalski. 8 Similarly, Han and Koh 23 found an approximately 40% decrease in antioxidant activity in dough compared to flour samples.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 93%